Prevalence, symptomatic features, and factors associated with sleep disturbance/insomnia in Japanese patients with type-2 diabetes - Narisawa H (Dove Medical Press, 2017)
Hajime Narisawa,1 Yoko Komada,1 Takashi Miwa,2 Junpei Shikuma,2 Mamoru Sakurai,2 Masato Odawara,2 Yuichi Inoue1,3 1Department of Somnology, 2Department of Diabetes, Endocrinology and Metabolism, Tokyo Medical University, Shinjuku-ku, 3Japan Somnology Center, Institute of Neuropsychiatry, Shibuya-ku, Tokyo, Japan Purpose: To clarify the prevalence and symptomatic characteristics of sleep disturbance/insomnia among type-2 diabetes mellitus (DM) Japanese patients.Methods: A cross-sectional survey of Japanese patients with the disorder was conducted. Participants consisted of 622 type-2 DM patients (mean 56.1±9.56 years) and 622 sex- and age-matched controls. Participants’ scores in the Japanese version of the Pittsburgh Sleep Quality Index (PSQI-J), the Japanese version of the 12-item Center for Epidemiologic Studies Depression Scale (CES-D), the Medical Outcomes Study 8-item Short Form Health Survey (SF-8), and the glycated hemoglobin A1c (HbA1c) of type-2 DM patients were analyzed.Results: There were 253 poor sleepers (43.9%) in the type-2 DM group as a result of dichotomization with the PSQI-J cutoff total score of 5.5. The type-2 DM group recorded a higher mean PSQI-J total score (P<0.01) and manifested poorer sleep maintenance. Poor sleepers in both groups had lower mental component summary from SF-8 (MCS), physical component summary from SF-8 (PCS), and CES-D than good sleepers, and good sleepers in both groups had higher MCS, PCS, and CES-D than poor sleepers. Higher body mass index, presence of smoking habit, and living alone were significantly associated with sleep disturbance/insomnia symptoms, but HbA1c was not associated with sleep disturbance/insomnia in the type-2 DM group.Conclusion: Individuals affected with type-2 DM are likely to experience sleep problems, characterized by disturbance in sleep maintenance. Sleep disturbance/insomnia symptoms in DM patients might considerably reduce health-related quality of life. Keywords: cross-sectional survey, depression, glycated hemoglobin A1c, quality of life, subjective sleep quality